Implementasi Aplikasi Pencatatan Data Magang Mahasiswa Berbasis Mobile Menggunakan Kodular Menggunakan Metode Waterfall - Alda, Muhamad; Wanandi, Bagus Sopian; Haryanzelina Bancin; Panjaitan, Mira Aripin (Bulletin of Computer Science Research, 2023)
This research aims to develop a mobile application for recording student internship data by applying a software development approach using the Waterfall model. The Waterfall model, known for its linear and structured stages, was chosen to ensure that the development process was carried out in an organized and documented manner. The main objective of this research is to implement a mobile application using the Kodular platform with a focus on recording student internship data, with the hope of increasing efficiency, accuracy and monitoring of internship activities. This research adopts the Waterfall model through the stages of analysis, design, implementation, testing and maintenance. The analysis stage is carried out to understand the needs and objectives of the application in depth, while the design stage is focused on the required structure and functionality. The implementation phase involves transforming the design into an optimally functioning mobile application. Testing is carried out to ensure application stability and performance, while maintenance is carried out to respond to changing needs or technology updates. By integrating the Waterfall model, this research aims to provide a structured framework that ensures each development stage is carried out carefully. It is hoped that the results of this research can create an efficient mobile application for recording student internship data, so that it can make a positive contribution in increasing efficiency and monitoring internship activities as a whole. Apart from that, this research can also be a reference for future mobile application developers who want to adopt the Waterfall model for similar projects, taking into account special needs and characteristics in the context of recording student internship data.